1993
DOI: 10.1017/s0031182000079464
|View full text |Cite
|
Sign up to set email alerts
|

Rapid changes in the surface of parasitic nematodes during transition from pre- to post-parasitic forms

Abstract: All mammalian-parasitic stages of a range of nematode species investigated (Brugia pahangi, Acanthocheilonema viteae, Strongyloides ratti, Nippostrongylus brasiliensis, Trichinella spiralis and Ostertagia ostertagi) labelled in a surface-restricted manner with the fluorescent lipid analogues 5-N-(octadecanoyl)aminofluorescein (AF18) or nitrobenzoxadiazole-cholesterol (NBD-chol), but failed to bind other similar probes. In contrast, the surfaces of the 'pre-parasitic' infective stages of these species had affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Nematodes can alter their surface composition in response to environmental signals, and evidence for this switching has been observed in changes in surface antigens, as well as changes in surface lipophilicity (Proudfoot et al, 1993;Olsen et al, 2007). Caenorhabditis elegans, widely studied as a model for environmental induction of surface changes, was found to switch its surface antigens based on environmental cues, and the switch involved chemosensory neurons (Grenache et al, 1996;Olsen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes can alter their surface composition in response to environmental signals, and evidence for this switching has been observed in changes in surface antigens, as well as changes in surface lipophilicity (Proudfoot et al, 1993;Olsen et al, 2007). Caenorhabditis elegans, widely studied as a model for environmental induction of surface changes, was found to switch its surface antigens based on environmental cues, and the switch involved chemosensory neurons (Grenache et al, 1996;Olsen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…3). The expression of these genes peak after change in surface lipophilicity (about 30 minutes) and commitment to exit (about 1 hour), but before many morphological and behavioral changes, such as pharyngeal pumping (about 3 hours) and increase in the diameter of the worm (Cassada and Russell, 1975;Golden and Riddle, 1984;Proudfoot et al, 1993). These genes could be an early transcriptional response that sets up the dauer recovery process.…”
Section: Transientmentioning
confidence: 99%
“…Upon transfer to favorable conditions, the first visible change is a change in surface lipophilicity (30 minutes), and commitment to dauer recovery occurs after approximately 50-60 minutes (Golden and Riddle, 1984;Proudfoot et al, 1993). Pharyngeal pumping, movement and increased body volume occur within 3 hours at 25°C (Cassada and Russell, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The noncollagenous epicuticle is exceedingly thin, and electron microscopy reveals little of its structure. Lipid analog probes associate with the epicuticle of many nematodes, but the probes do not diffuse as they do in a cellular lipid bilayer, implying a different type of organization (Proudfoot et al 1993). A biochemical study of the C. elegans surface suggested that the epicuticle contains a heterodimeric protein complex (Blaxter 1993).…”
mentioning
confidence: 99%